Both dorsal and ventral attention network nodes are implicated in exogenously driven visuospatial anticipation. (August 2019) - Ahrens, Merle-Marie; Veniero, Domenica; Freund, Inga Marie; Harvey, Monika; Thut, Gregor
Abstract: Neuroimaging and transcranial magnetic stimulation (TMS) studies have implicated a dorsal fronto-parietal network in endogenous attention control and a more ventral set of areas in exogenous attention shifts. However, the extent and circumstances under which these cortical networks overlap and/or interact remain unclear. Crucially, whereas previous studies employed experimental designs that tend to confound exogenous with endogenous attentional engagement, we used a cued target discrimination paradigm that behaviourally dissociates exogenous from endogenous attention processes. Participants engaged with endogenous attention cues, while simultaneous apparent motion cues were driving exogenous attention along the motion path towards or away from the target position. To interfere with dorsal or ventral attention networks, we delivered neuronavigated double-pulse TMS over either right intraparietal sulcus (rIPS) or right temporo-parietal junction (rTPJ) towards the end of the cue target interval, and compared the effects to a sham-TMS condition. For sham-TMS, endogenous and exogenous cueing both benefitted discrimination accuracy. Target discrimination was enhanced at validly versus invalidly cued locations (endogenous cueing benefit) as well as when targets appeared in versus out of the motion path (exogenous cueing benefit), despite motion being uninformative and task-irrelevant, replicating previous findings. Interestingly, both rIPS- and rTPJ-TMS abolished attention benefits from exogenous cueing, while endogenous cueing benefits were unaffected. Our findings provide evidence against independent involvement of the dorsal and ventral attention network nodes in exogenous attention processes.